Usos das fontes digitais: uma análise de teses e dissertações de programas de Pós-Graduação em História no Rio Grande do Sul (2015 – 2017) - Frigo, Denise (2022)
In this thesis, the results of the research, developed in the Postgraduate Program in History, in the research line Culture, Migrations and Work, are presented. The project is inserted in this line, since the cultural transformations of the production of digital sources, which occurred during the 21st century, are analyzed in the historian's research methodology. The objective of this thesis is to methodologically analyze the insertion of digital documents as sources in historical research, from the context of the Postgraduate Programs in History, of the Universities of Rio Grande do Sul, in the period from 2015 to 2017. In the second chapter, we seek to present the construction of the thesis and, using bibliographical research, we address the state of the art of the theme. In the third chapter, of bibliographical discussion, some connections made by historians in the act of making history with the internet are exposed, and in continuity, a panorama of the historical source is shown, its conceptualization, starting from the digital, and the context of the changes that have occurred in recent years. The theme of the fourth chapter is the historical source, its conceptualization in the digital age, and the context of the changes that have taken place in recent years, based on bibliographical research. To this end, it begins with the history of the concept of sources. Next, some categories of digital sources are conceptually explored. Another sub-chapter is dedicated to the possibilities and challenges that the use of digital sources can pose to historians in their research. The fifth chapter is a reflection based on the theses and dissertations, in which it is possible to perceive trends, repetitions, recurrent patterns, variations, and to foster the theoretical and practical grounding of historians, that is, an initial approach to the object through a mapping of the research. In this chapter, a textual analysis is carried out, based on the citations, using the Voyant Tools tool, and on the content, through a full reading of the academic productions. The sixth and last chapter refers to the discussions of the results of the questionnaires in relation to digital sources and the perception of the doctors and masters in History. We conclude by demonstrating that the theme of digital sources has been absent from the methodological debates cited in historiographical productions. Thus, the incorporation of digital sources in historical research requires more methodological awareness and self-criticism, since one must try to fully understand the risks of all the choices made and present the procedures followed in all stages of the research. In this thesis, the results of the research, developed in the Postgraduate Program in History, in the research line Culture, Migrations and Work, are presented. The project is inserted in this line, since the cultural transformations of the production of digital sources, which occurred during the 21st century, are analyzed in the historian's research methodology. The objective of this thesis is to methodologically analyze the insertion of digital documents as sources in historical research, from the context of the Postgraduate Programs in History, of the Universities of Rio Grande do Sul, in the period from 2015 to 2017. In the second chapter, we seek to present the construction of the thesis and, using bibliographical research, we address the state of the art of the theme. In the third chapter, of bibliographical discussion, some connections made by historians in the act of making history with the internet are exposed, and in continuity, a panorama of the historical source is shown, its conceptualization, starting from the digital, and the context of the changes that have occurred in recent years. The theme of the fourth chapter is the historical source, its conceptualization in the digital age, and the context of the changes that have taken place in recent years, based on bibliographical research. To this end, it begins with the history of the concept of sources. Next, some categories of digital sources are conceptually explored. Another sub-chapter is dedicated to the possibilities and challenges that the use of digital sources can pose to historians in their research. The fifth chapter is a reflection based on the theses and dissertations, in which it is possible to perceive trends, repetitions, recurrent patterns, variations, and to foster the theoretical and practical grounding of historians, that is, an initial approach to the object through a mapping of the research. In this chapter, a textual analysis is carried out, based on the citations, using the Voyant Tools tool, and on the content, through a full reading of the academic productions. The sixth and last chapter refers to the discussions of the results of the questionnaires in relation to digital sources and the perception of the doctors and masters in History. We conclude by demonstrating that the theme of digital sources has been absent from the methodological debates cited in historiographical productions. Thus, the incorporation of digital sources in historical research requires more methodological awareness and self-criticism, since one must try to fully understand the risks of all the choices made and present the procedures followed in all stages of the research.